Neuronal and Synaptic Plasticity in the Visual Thalamus in Mouse Models of Glaucoma - Van Hook, Matthew J.; Monaco, Corrine; Bierlein, Elizabeth R.; Smith, Jennie C. (Frontiers in Cellular Neuroscience, 2021)
Homeostatic plasticity plays important roles in regulating synaptic and intrinsic neuronal function to stabilize output following perturbations to circuit activity. In glaucoma, a neurodegenerative disease of the visual system commonly associated with elevated intraocular pressure (IOP), early disease is associated with altered synaptic inputs to retinal ganglion cells (RGCs), changes in RGC intrinsic excitability, and deficits in optic nerve transport and energy metabolism. These early functional changes can precede RGC degeneration and are likely to alter RGC outputs to their target structures in the brain and thereby trigger homeostatic changes in synaptic and neuronal properties in those brain regions. In this study, we sought to determine whether and how neuronal and synaptic function is altered in the dorsal lateral geniculate nucleus (dLGN), an important RGC projection target in the thalamus, and how functional changes relate to IOP. We accomplished this using patch-clamp recordings from thalamocortical (TC) relay neurons in the dLGN in two established mouse models of glaucoma – the DBA/2J (D2) genetic mouse model and an inducible glaucoma model with intracameral microbead injections to elevate IOP. We found that the intrinsic excitability of TC neurons was enhanced in D2 mice and these functional changes were mirrored in recordings of TC neurons from microbead-injected mice. Notably, many neuronal properties were correlated with IOP in older D2 mice, when IOP rises. The frequency of miniature excitatory synaptic currents (mEPSCs) was reduced in 9-month-old D2 mice, and vGlut2 staining of RGC synaptic terminals was reduced in an IOP-dependent manner. These data suggest that glaucoma-associated changes to neuronal excitability and synaptic inputs in the dLGN might represent a combination of both stabilizing/homeostatic plasticity and pathological dysfunction.